2022
DOI: 10.1590/1413-7054202246022321
|View full text |Cite
|
Sign up to set email alerts
|

Tilapia nursery stocking densities in a chemoautotrophic biofloc system

Abstract: The nursery phase in tilapia using biofloc technology is important as it increases the predictability of production. However, none studies evaluating the stocking densities of tilapia focused only on the use of an inorganic carbon source to promote the nitrification process as the main way to control nitrogen in the system. This study aimed to evaluate the effect of varied nursery stocking densities, in a chemoautotrophic biofloc system, on water quality, zootechnical parameters, and health of Nile tilapia (Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The differences between densities among the parameters measured during production were not significant. Similarly, in studies where Nile tilapia were maintained at densities of 800 fingerlings/m³ (average weight: 18 g) and evaluated in nurseries for 44 days, the water quality parameters were maintained; however, the production of decanting solids and biomass was more efficient at densities of 406 fish/m³ (Silva et al, 2022). because more fish occurred in the T40 group; therefore, although the weight of each fish was lower, the total biomass was greater in the T40 group than in the T30 group.…”
Section: Resultsmentioning
confidence: 99%
“…The differences between densities among the parameters measured during production were not significant. Similarly, in studies where Nile tilapia were maintained at densities of 800 fingerlings/m³ (average weight: 18 g) and evaluated in nurseries for 44 days, the water quality parameters were maintained; however, the production of decanting solids and biomass was more efficient at densities of 406 fish/m³ (Silva et al, 2022). because more fish occurred in the T40 group; therefore, although the weight of each fish was lower, the total biomass was greater in the T40 group than in the T30 group.…”
Section: Resultsmentioning
confidence: 99%
“…Poor water conditions can also inhibit fish growth performance. Aquaculture ponds that contain high particles from the left-over feed and fish excretion can increase the NH3, NO2, TDS in water, and decrease the pH and DO, which all these parameters are needed to be in the optimum level to accelerate the fish growth (de Silva et al, 2022;Laza et al, 2021;Setyono et al, 2023). Studies have shown that exposure to suspended sediments can impact the gill structure and microbiome of fish larvae, potentially influencing the distribution patterns of fish assemblages (Hess et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, using low stocking densities may not be economically viable, resulting in lower productivity per unit area and ine cient use of natural resources, leading to reduced biomass production (Inoue et al, 2014;Silva et al, 2022).…”
Section: Introductionmentioning
confidence: 99%